(untitled) (Fiep Bulletin - online, 2013)
The social organization of the work involves addition to physical, institutional, cultural, industrial/ practical spaces, the interactions of individuals between them, are directly related to the environment and the conditions where it is performed. This is an exploratory comparative study composed of 74 adult fishermen, being 33 Portuguese and 44 Brazilians, of both sexes, with different school of free schooling, to complete the second degree. As a tool was used in a semi-structured, the technique of free evocation of words (inducing words: work of fishing and health), and observation patchy. The results show that the Brazilian and Portuguese represent their work differently: ’fishing’ and ’danger, sacrifice and survival, respectively. These senses can denote certain conformism, corroborated by observing a situation where they seized from housing and precarious living without pleasure, with a fairly high rate of alcoholism.